Analysis of MEP Work Waste Management Efforts in Building Construction Projects in Jakarta Greater Area - Augustin, Elfira; Karlinasari, Lina; Erizal, (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Construction projects are among the sectors that are growing rapidly in Indonesia and have an impact on the environment from the resulting construction waste. The purpose of this study is to analyze the highest type and quantity of construction waste generated from Mechanical Electrical Plumbing (MEP) work from the difference in the amount of material from the BOQ with the amount attached to the as-built drawings, evaluate the economic value by calculating the ratio of the amount of waste generated to the amount of material at BOQ (waste level) × the scope of work percentage (waste cost), selling value of waste (the quantity of waste × the local selling price), and costs of disposal of construction waste based on the agreement of each project management. This study uses a descriptive quantitative method. The results showed that most of the construction waste generated was based on its type, consisting of copper-based cables, steel and plastic pipes, and polyurethane ducts. The highest quantity of construction waste came from the office project, which was 2 × 1.5 mm2 NYA cables (216,515 m). The highest waste level value came from office, condotel, and factory projects using several types of cables (> 94%). The highest waste cost value came fromthe condotel project is polyurethane duct (IDR 5,727,267,000.00). The metal waste produced is sold by contractors to collectors for recycling. Non-metal waste is disposed by paying a civil contractor. Construction waste management policies must be implemented to reduce the amount and impact of construction waste generated.